Synthesis of CuZn MOF MXene as an antibacterial coating on contact lens - Saleem, Misbah (My University, 2025)
The benefits and convenience of contact lenses are accompanied by few complications. Contact Lens Complications (CLC) includes microbial keratitis, blepharitis, fungal infections, acanthamoeba keratitis, herpes simplex keratitis, herpes zoster keratitis and marginal keratitis. Wearing contact lenses for the extended duration without taking proper cleaning measures, elevate the possibility of bacterial growth on it. The conjunctivitis and keratitis are associated with microbial keratitis caused by certain Gram-positive and Gram-negative bacteria. This research majorly focused on Staphylococcus aureus (S. aureus) and Escherichia coli (E.coli), which are the significant bacteria in originating the eye infection. This research comprehends on the introduction of CuZn MOF based MXene, on contact lenses to prevent bacterial growth. Ti3C2Tx MXene was coupled with methyl imidazole based CuZn MOF, as the MOF derived composites exhibits high antibacterial activity (Mofei Shen, 2020). MOF were prepared using Zinc(II) nitrate hexahydrate, Copper(II) nitrate trihydrate, methylimidazole and methanol. These MOF composites were than combined and analyzed with four different concentrations (1mg/ml, 500µg/ml, 250µg/ml 125µg/ml and 62.5µg/ml) of MXene using magnetic stirrer for overnight. The CuZn-MXene composite was later analyzed using SEM, TEM, FTIR and XRD. The antibacterial activity of this MXene composite was tested on E.coli and S. aureus bacteria by colonies growth on nutritive agar plates. Subsequently, the contact lens were also prepared by combining cross linker polymer, lithium phenyl 2,4,6 trimethyl benzoyl phosphate (LAP), merged with hyaluronic acid methacrylate (HAMA) and deionized water.
Keywords: MXene, metal organic framework, CuZn, contact lens, ocular diseases